ASSESSMENT OF ENVIRONMENTAL AND ENGINEERING GEOLOGICAL PROBLEMS FOR THE POSSIBLE RE-USE OF AN ABANDONED ROCK-HEWN SETTLEMENT IN URGüP (CAPPADOCIA), TURKEY - Ulusay R.; Gokceoglu C.; Topal T.; Sonmez H.; Tuncay E.; Erguler Z.A.; Kasmer O. (My University, 2006)
The Cappadocia Region of Central Anatolia having a very distinct culture is one of the attractive touristic sites of Turkey due to its spectacular and unique landforms and historical heritages. In this region, the structures carved into thick to massive tuffs survived and kept their original integrity for a number of centuries. Environmental and anthropological factors at the Cappadocia Region have been the main reasons for extensive subsurface and multi-purpose use in the past and present. In addition, thermal insulation properties of the tuffs make these rocks suitable for use in underground openings. The Kayakapi Neighborhood, located in the town of Urgüp, is one of the famous historical sites. This site is situated within the “Göreme National Park and the Rock Sites of Cappadocia” which was inscribed on the World Heritage List in 1985. In order to develop the tourism potential of this abandoned site while preserving its cultural and natural values, a natural environmental conservation and revitalization project was initiated. As an integral part of this project, in this study, environmental and engineering geological problems, including rock fall potential and stability of about 1,200 rock-hewn structures, were investigated and an inventory was prepared for the possible re-use of the underground openings and other structures at the site, and remedial measures were recommended. The assessments based on observations and experimental studies indicated that the tuffs do not show significant changes both perpendicular and parallel to layering, and discontinuities and rock weathering seem to be more important factors controlling the stability of rock-hewn structures. The major stability problems threatening the re-use of the openings are structurally-controlled block instabilities, overbreaks, and erosion and shearing of the pillars made of tuff. On the other hand, the area at the entrance of the site requires some protection measures such as the construction of a retaining wall, systematic bolting of rock slabs and removal of some blocks having rock fall potential. The inventory for the openings suggests that there are a number of openings that can be re-used after necessary remedial measures.
Keywords: CAPPADOCIA; ENVIRONMENTAL CONDITIONS; KAYAKAPI (URGüP); ROCK FALL; STABILITY OF UNDERGROUND OPENING; TROGLODYTE; TUFF